A comparative study of femtosecond pulsed laser ablation of meloxicam in distilled water and in air - Eszter Nagy; Judit Kopniczky; Tamás Smausz; Máté Náfrádi; Tünde Alapi; János Bohus; Viktor Pajer; Piroska Szabó-Révész; Rita Ambrus; Béla Hopp (Scientific Reports, 2023)
Abstract The increasing prevalence of water insoluble or poorly soluble drugs calls for the development of new formulation methods. Common approaches include the reduction of particle size and degree of crystallinity. Pulsed laser ablation is a clean technique for producing sub-micrometre sized drug particles and has the potential to induce amorphization. We studied the effect of femtosecond pulsed laser ablation (ELI ALPS THz pump laser system: λc = 781 nm, τ = 135 fs) on meloxicam in distilled water and in air. The ablated particles were characterized chemically, morphologically and in terms of crystallinity. We demonstrated that femtosecond laser ablation can induce partial amorphization of the particles in addition to a reduction in particle size. In the case of femtosecond pulsed laser ablation in air, the formation of pure meloxicam spheres showed that this technique can produce amorphous meloxicam without the use of excipients, which is a unique result. We also aimed to describe the ablation processes in both investigated media.